European consumers' perception of moderate wine consumption on health - Riccardo Vecchio; Giulia Decordi; Léa Grésillon; Claire Gugenberger; Margot Mahéo; Frédérique Jourjon (Wine Economics and Policy, 2017)
The present study examines the perceptions that French, Italian and Spanish consumers have about the possible health effects of what they consider to be a moderate wine consumption. Furthermore, it identifies whether the following factors positively or negatively influence consumer opinion - wine appreciation, environmental awareness, environmental labels, local legislation and media coverage. Perceptions were identified through an online survey of 1183 respondents. The respondents perceive wine as a rather healthy product if consumed moderately. Wine appreciation positively influences the perception of a healthy effect of moderate wine consumption. French policies advising constraints on wine consumption indirectly influence consumer opinion about the unhealthy effects caused by wine. French and Spanish consumers with high environmental awareness perceive a wine with an eco-label to be healthier than a conventional one.
Keywords: 330; France; Health; Italy; Moderate consumption; Spain; Wine